Association of Self-management and Social Support among Stroke Patients - Fengguang GUAN; Mei WANG; Xiaoqin LIAN (康复学报)
Objective:To explore the influence of social support level on self-management behavior of convalescent patients with stroke, so as to provide an effective method to construct the self-management model for recovery stage stroke patients.Methods:The research investigated 440 hospitalized patients in stroke recovery stage effectively by employing social support rating scale and self-management behavior rating scale.Results:The total score of social support was (40.27±7.50), self-management behavior score was (151.95±23.58), and three dimensions of objective support, subjective support and the utilization of support all had positive correlation with the self-management behavior of the patients.Conclusion:The self-management behavior of stroke patients and the level of social support are related in the recovery stage.